But I'm a cheerleader [videorecording (DVD)] - Lyonne, Natasha; Du Vall, Clea; Basco, Dante, 1975-; RuPaul, 1960-; Babbit, Jamie, 1970- (Lion's Gate Home Entertainment, 2003)
Megan's super normal suburban existence is filled with friends, pom-poms and rah-rah enthusiasm until her parents suspect that she may be showing deviant tendencies.